Factors that infl uence the mechanical, physical and thermal properties of wood-plastic composite materials (2018)
This paper presents a general review of the use of plastic and lignocellulosic waste in the production of Wood Plastic Composites (WPC). Wood-Plastic Composites are proposed as a solution to the growing generation of waste. Diff erent mixtures of polymer matrices (plastics) and vegetable reinforcements (lignocellulosic residues) have been evaluated for the WPC production. The mixing of this type of raw material is mainly done using three types of technologies: extrusion, injection and compression molding. It was found that changes in the mechanical properties of the fi nal product depend on the raw material type, the particle size and the fiber proportion used, as well as the addition of binding agents. In the same way, variations in the water absorption capacity, densifi cation and thermal stability of the fi nal compound are reported to increase the amount of fi ber in the mixture.